Ответы и объяснения

  • Участник Знаний
2013-05-08T08:39:21+04:00

2X - 2Y - 7X = 13

- 5X - 2Y = 13

//////////////////////

15X + 3X + 3Y = - 9

18X + 3Y = - 9

////////////////////

13X + Y = 4

Y = 4 - 13X

////////////////////

18X + 3*(4 -1 3X) = - 9

18X + 12 - 39X = - 9

 - 21X = - 21

X = 1

/////////////////

Y = 4 - 13 = - 9

 

2013-05-08T15:17:20+04:00

2(x-y)-7x=13

15x+3(x+y)=-9

 

2(x-y)-7x=13

y=-2.5x-6.5

15x+3(x+y)=-9 

15x+3(x+(-2.5x-6.5))=-9

15x-4.5x-19.5+9=0

10.5x-10.5=0

x=10.5/10.5

x=1

2(x-y)-7x=13
2(1-y)-7*1=13

3. -18-2y=0

y=-18/2

y=-9